Venus: Trends in the Numismatic Commemoration of the State Goddess - Ryan, Caitlin (My University, 2016)
Venus is one of the most famous goddesses of the Roman pantheon, known for her grace and beauty. Her likeness was recreated countless times in a variety of different media. She was depicted in many ways on coinage, and was called several different names by the inscriptions: Venus Genetrix, Venus Felix, and Venus Victrix. By studying the whole collection of coins of Venus from the late Republican period through AD 192, it is possible to gain an understanding of how depiction of the goddess corresponded to the title she was given on that coin. Using that information, one can then determine which aspect of Venus is represented in unlabelled images of her. Similarly, the data can be used to critique scholarly opinions on the original appearances of the lost cult statues of Venus Genetrix, Felix, and Victrix. There is a fair bit of overlap between the attributes of Venus Genetrix and Felix, as they share the common image of the goddess holding an apple. However, depictions of the deity holding an infant or unveiling herself are unique to Venus Genetrix, and images of birds are not seen on coins with epithets other than Venus Felix. Venus Victrix is the only aspect of the goddess to be shown with Mars on coinage, although this happens only rarely. Otherwise, she can be difficult to differentiate from other aspects of Venus. With observations such as these and others in mind, scholarly suggestions about the appearances of the lost cult statues seem less credible, and more open for debate.
Keywords: Rome; Art; Deity